Avaliação da detoxificação de associações de lodos de ETE e ETA pelo bioensaio de Allium cepa - Santos, Tamara [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Water Treatment Plants (WTP) and Sewage Treatment Plants (STP) use methodologies to ensure the quality of water for the population and to reduce the impacts of xenobionts on water bodies. However, the treatment processes generate waste, called treatment sludge. They can be discarded without treatment in water bodies or, if treated, sent to landfills, generating a high cost for the stations. Sewage sludge (SS) has beneficial characteristics to be reused in agriculture as fertilizers or as soil reconditioners successively used in crops due to its large amounts of organic matter. However, the use of this waste without adequated pretreatment can have negative impacts on the environment, as it may contain harmful substances, such as metals and potentially toxic organic compounds. Sludge from Water Treatment Plants (SW) has been used in some countries in the area of civil construction and citrus crops, but in Brazil few studies have considered the benefits of using SW in agriculture. Bioremediation is a process used in waste treatment, which uses microorganisms capable of decomposing pollutants. The aim of this study was to evaluate the efficacy of the bioremediation process for a period of 6 months in the detoxification of WTP and STP sludge, through Allium cepa test. The phytotoxic, cytotoxic, genotoxic and mutagenic potentials of pure sludge samples (SW and SS), of association between SW and SS and combinations of both sludges with soil, before and after the bioremediation process, were evaluated in this study. At the initial time of the experiment (T0), the treatments performed with SW; SW+S; SW+SS samples inhibited the germination of A. cepa seeds. However, the radicles of the few seeds that germinated did not reach enough length for the accomplishment of the ecotoxicogenetic tests. Regarding the results of cytotoxicity and mutagenicity for T0, the treatments were not significant when compared with the results of the negative control (NC) test...

As Estações de Tratamento de Água (ETA) e as Estações de Tratamento de Esgoto (ETE) usam metodologias que visam garantir a qualidade da água a ser disponibilizada para a população e minimizar impactos dos resíduos sobre os corpos d'água. Contudo, os processos de tratamentos geram resíduos, denominados de lodo de tratamentos. Esses resíduos, quando não previamente tratados, são descartados em corpos d'água ou, após tratamento, enviados para aterros sanitários, gerando alto custo para as estações de tratamento. O lodo de esgoto (LE) apresenta características favoráveis para ser reutilizado na agricultura como fertilizantes ou recondicionantes de solos desgastados, por conter grandes quantidades de matéria orgânica. Porém, o uso desse resíduo sem tratamento prévio adequado pode causar impactos negativos no ambiente, por ele também pode conter substâncias nocivas, como metais e compostos orgânicos potencialmente tóxicos. O lodo proveniente das ETAs (LA) vem sendo empregado em alguns países na área de construção civil e na produção de citrus, entretanto no Brasil poucos estudos avaliaram os benefícios do uso do LA na agricultura. A biorremediação é um processo usado em tratamento de resíduos, que utiliza microrganismos capazes de decompor poluentes. Este estudo teve como objetivo avaliar a eficácia do processo de biorremediação, por um período de 6 meses, na detoxificação dos lodos de ETE (LE) e ETA (LA), por meio do ensaio com Allium cepa. Foram avaliados neste estudo os potenciais fitotóxicos, citotóxicos, genotóxicos e mutagênicos de amostras de lodos puros (LA e LE), de associação entre LA e LE e associações dos dois lodos com solo, antes e após o processo de biorremediação. No tempo inicial do experimento (T0), os tratamentos realizados com LE; LE+S; LE+LA inibiram a germinação das sementes de A. cepa. Contudo, as radículas das poucas sementes que germinaram não atingiram...
Keywords: Resíduos; Resíduos sólidos; Biorremediação; Toxicologia genética; Lodo de esgoto; Cebola; Água - Estações de tratamento; Água - Qualidade; Agricultura; Cromossomos - Aberrações; Residuos organicos como fertilizantes